Tracing interacting literacy practices in master's dissertation writing (UCL Press, 2017)
Academic literacy practices are increasingly varied, influenced by the diverse education and language backgrounds of students and staff, interdisciplinary approaches, and collaborations with non-university groups such as business partners. Completing a master's dissertation thus requires students to negotiate literacy practices associated with different domains. To enable an investigation of conditions for such negotiations, this article extends the concept of literacy practices by combining insights from Academic Literacies, New Literacy Studies and Schatzki's (1996) social practice ontology. The resulting framework is applied in a case study of a student who negotiates academic requirements and entrepreneurial goals in completing a master's dissertation.